Innovative and Affordable Feed Solutions for Enhancing Cattle Finishing in Tanzania (Global Journal of Science Frontier Research, 2025)
In Tanzania, livestock significantly contributes to the national economy, with the beef sub-sector accounting for 2.2% of the GDP. However, unfinished cattle at slaughterhouses result in suboptimal beef quality. Proper finishing is crucial because it adds value to the quality of beef meat. Apart from genetics, applying the right feed technology and feeding strategies on beef cattle before slaughter can increase output by 70% and perhaps coequal with health. The current study developed two feed diet formulas using local feed materials given the high quality and affordable cost for the Zebu cattle finishing business.
Keywords: cattle; finishing; fattening; feed formula; diet